The multivalued penalty method for evolution variational inequalities with λ₀-pseudomonotone multivalued maps - Kasyanov, P.O.; Mel'nik, V.S.; Toscano, L. (Нелінійні коливання, 2007)
We consider evolution variational inequalities with λ₀-pseudomonotone maps. The main
properties of the given maps have been investigated. By using the finite differences method,
strong solvability for the class of evolution variational inequalities with λ₀-pseudomonotone
map has been proved. Using the penalty method for multivalued maps, the existence of weak
solutions for evolution variation inequalities on closed convex sets has been shown. The class
of multivalued penalty operators has been constructed. We also consider a model example to
illustrate the given theory. Розглядаються еволюцiйнi варiацiйнi нерiвностi з λ₀-псевдомонотонними вiдображеннями. Доведено основнi властивостi даних вiдображень. За допомогою методу скiнченних рiзниць встановлено „сильну” розв’язнiсть для класу еволюцiйних варiацiйних
нерiвностей з λ₀-псевдомонотонними вiдображеннями. За допомогою методу штрафа доведено iснування слабкого розв’язку для еволюцiйних варiацiйних нерiвностей на
замкнених опуклих множинах. Побудовано клас багатозначних операторiв штрафа.
Наведено модельний приклад, який iлюструє дану теорiю.